Kepemimpinan Perempuan dan Kesetaraan Gender: Sebuah Tinjauan - Malihah, Lola; Zabidi, Haya; Atkia, Noor; Apifah, Nida Nor; Haryanti, Peni (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In this era of globalization, paradigm changes occur in several aspects of life, one of which is in the field of human resources, especially leadership. In the past, leadership was only identified with men, but now many women are starting to occupy high positions as leaders. This article is a review that examines various challenges in women's leadership. Data was obtained from literature studies from various reference sources such as books, articles published in journals and other relevant sources. The results obtained show that there are efforts to realize equal rights and gender equality, so that women's opportunities to become leaders are not limited. Several women have succeeded in occupying strategic positions in both the political, economic and educational fields. However, there is still an opinion that opportunities for women are more due to policies that require women's representation, not because of their competence. Of course, this is completely unfounded, considering that women are also able to compete with men in terms of performance so that there is no longer any negative discriminatory treatment towards women. In the Islamic paradigm, women's position is equal to men. Even from an Islamic perspective, there are several aspects that still do not allow a woman to lead, such as being an imam during prayer. Meanwhile, from a social and cultural perspective, the patriarchal paradigm still applies in some communities, thereby limiting opportunities for women to become leaders.